The Development of Multivariate Statistical Process Monitoring (MSPM) Tools using Microsoft® Excel - Che Elliaziz, Mohd Syaufi (Universiti Teknologi PETRONAS, 2009)
Multivariate statistical process control methods have been proven in the process industries to be an effective tool for process monitoring, modelling and fault detection.This paper describes the approach used by the writer in the development of a Multivariate Statistical Process Monitoring (MSPM) tools using Microsoft Excel. This developed MSPM tools will act as a process monitoring tools in order to monitor the performance of any equipment or process. In addition, this project will be testing on actual plant data to see the performance of the project. The tool will be developed in Microsoft Excel and Matlab. Microsoft Excel is chosen because of it is easy to use and user-friendly. Furthermore, it has macro function and easier to use when the user wants to develop many tools to the Microsoft Excel. In multivariate statistical process monitoring, a process monitoring model must be developed firstly. The model must be free from any abnormality, fault or outliers. Then the model will be tested on the future data to detect any abnormality in the process by applying the appropriate Hmits. As a conclusion, the MSPM method can be develop in Microsoft Excel. This tool can help to detect the problem or abnormality of the process and help in diagnoss assignable cause for the process IV